On Approximation Orders of Functions of Several Variables in the Lorentz Space - Akishev, G. (Pleiades Publishing, 2018)
We consider the anisotropic Lorentz space of periodic functions. Sufficient conditions are proved for a function to belong to the anisotropic Lorentz space. Estimates for the order of approximation by trigonometric polynomials of the Nikol’skii–Besov class in the anisotropic Lorentz space are established.
Keywords: Lorentz space; Nikol’skii–Besov class; best approximation